ANALISIS DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN BPJS MANDIRI RAWAT JALAN PADA RUMAH SAKIT BINA KASIH MEDAN - Sagala, Roslinda; Marbun, Gembira (UNIKA Santo Thomas, 2022)
The purpose of this study was to analyze the effect of service quality consisting of reliability, responsiveness, assurance, tangible, partial and simultaneous empathy on inpatient satisfaction at Bina Kasih General Hospital Medan. . The population of all BPJS Mandiri patients hospitalized at Bina Kasih Hospital, Medan. The sample is 96 respondents, the data collection method is through questionnaires and documentation, the analysis method is multiple regression. The regression equation: KP = 2.641 + 0.305K + 0.108Kt + 0.103Ky + 0.203B + 0.131E means that reliability, responsiveness, confidence, tangibles and empathy have a positive effect on patient satisfaction and the reliability dimension has a greater influence on inpatient satisfaction compared to other variables. The results of the F test indicate that reliability, responsiveness, confidence, tangibles and empathy have a simultaneous and significant effect on patient satisfaction, so H0 is rejected and H1 is accepted. The results of the t-test showed that reliability, responsiveness, confidence, tangibles and empathy had a partial and significant effect on patient satisfaction, so H0 was rejected and H1 was accepted. The value of the determinant coefficient (R Square) is 0.514, meaning that inpatient satisfaction can be explained by the dimensions of service quality (reliability, responsiveness, confidence, tangibles and empathy) of 51.4% while another 48.6% is explained by other unexplained factors. in this research such as security, promotion and communication. The Bina Kasih Hospital Medan should improve the quality of service regarding the variables of responsiveness, confidence/guarantee, tangible and empathy.